Thermoelectric response of quaternary Heusler compound CrVNbZn - Kara, H.; Kahaly, M. Upadhyay; Ozdogan, K. (ELSEVIER SCIENCE SA, 2018)
The electronic, magnetic and thermoelectric properties of CrVNbZn quaternary Heusler compound are investigated by means of first-principles calculations in combination with Boltzmann transport theory. The lattice is found to crystallize in the cubic quaternary Heusler structure (space group 216). As observed from the electronic bands near the Fermi level and corresponding densities of states (DOS), a prominent asymmetry in DOS is induced by V and Cr atoms followed by slight contribution from Nb. One sharp electronic band, with maximal contribution from V d electronic states, and just touching the Fermi level makes the system semiconducting, and enhances the thermoelectric figure of merit. The mechanism leading to this behavior is explained in terms of a local spin-polarization introduced by the V ions. Our results indicate that magnetic doping can play a strong role in tuning the electronic and magnetic properties of CrVNbZn compound, and in general in quaternary Heusler compounds. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Quaternary Heusler compound; Thermoelectrics; Strain effect; HALF-HEUSLER; MAGNETIC-PROPERTIES; SUBSTITUTION; PERFORMANCE; ALLOYS; FIGURE; MERIT; CODE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering